(untitled) (Doctor Virtualis, 2023)
The speculative system of Giovanni Scoto Eriugena is one of the most complexes in the medieval panorama. In the Periphyseon, his greatest systematic work, analogy occupies a central role. Following Neoplatonism, Eriugena uses analogy as a cosmic law that governs the procession of natures from the One and organizes the relationship between reality and its origin. In the proceeding of natures from One, however, the analogy is articulated as participation. The analogy is underlain as the foundation of dialectics as the art of reasoning, leading to a complex discourse on the relationship between dialectic and rhetoric. This article aims to analyze two issues in particular: what are the textual bases through which the medieval thinkers were able to use analogy as an argumentative and philosophical device; to investigate how, in the Eriugenian work, the analogy becomes both a method of representing the world and a cognitive device.